2020
DOI: 10.1002/csc2.20317
|View full text |Cite
|
Sign up to set email alerts
|

Fall‐armyworm invasion, control practices and resistance breeding in Sub‐Saharan Africa

Abstract: Fall armyworm [Spodoptera frugiperda (J.E. Smith); FAW] invasion has exacerbated maize (Zea mays L.) crop yield losses in sub‐Saharan Africa (SSA), already threatened by other stresses, especially those that are climate‐change induced. The FAW is difficult to control, manage, or eradicate, because it is polyphagous and trans‐boundary, multiplies fast, has a short life cycle and migrates easily, and lacks the diapause growth phase. In this study, FAW and its impact in Africa was reviewed, as well as past and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 91 publications
(290 reference statements)
0
47
0
Order By: Relevance
“…The effectiveness of botanical extracts (e.g., neem-based products) and mechanical control (e.g., killing larvae of the pest) received below-average scores. The FGD participants gave a low effectiveness score (two) for agro-ecological approaches (e.g., cropping systems such as intercropping), which were promoted to control FAW in Ethiopia and elsewhere [ 2 , 7 , 18 , 56 ]. This result is in line with a study in southern Ethiopia that found that intercropping (maize-legume) had little impact on controlling maize production losses due to FAW in southern Ethiopia [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of botanical extracts (e.g., neem-based products) and mechanical control (e.g., killing larvae of the pest) received below-average scores. The FGD participants gave a low effectiveness score (two) for agro-ecological approaches (e.g., cropping systems such as intercropping), which were promoted to control FAW in Ethiopia and elsewhere [ 2 , 7 , 18 , 56 ]. This result is in line with a study in southern Ethiopia that found that intercropping (maize-legume) had little impact on controlling maize production losses due to FAW in southern Ethiopia [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Maize is a staple food for more than 300 million Africans [ 1 , 2 ]. Despite the importance of maize, its production is constrained by several biotic and abiotic factors that contribute to sub-Saharan ‘Africa’s (SSA) pervasive food insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the maize transgenic event, MON89034, introduced in 2010 by Monsanto contained stacks of insect-resistance traits, and is resistant to FAW. These GM products were first commercialized in South Africa (Chandrasena et al, 2018;Matova et al, 2020).…”
Section: Gm Crops Resistant To Pathogens and Reduced Use Of Pesticides/ Insecticidesmentioning
confidence: 99%
“…Matova et al. (2020) described their efforts to breed fall armyworm ( Spodoptera frugiperda (J.E. Smith)) resistant maize.…”
Section: The Importance Of Plant Healthmentioning
confidence: 99%